PERENCANAAN DAN PENGEMBANGAN SUMBERDAYA TERHADAP INDUSTRI PARIWISATA DI KABUPATEN RAJA AMPAT, PAPUA BARAT - Hamsinah B. (Universitas Pamulang, 2016)
RESOURCE PLANNING AND DEVELOPMENT OF TOURISM INDUSTRY IN THE DISTRICT RAJA Ampat, West Papua. Raja Ampat tourism development, also developed in line with the determination of the application of Special Autonomy (Autonomy) in the Land of Papua. Enforcement of Law No. 21 of 2001, reinforced (asserted) Raja Ampat legitimacy of local governments to manage the potential areas in order to achieve development goals. Entry Special autonomy in Raja Ampat is expected to provide opportunities and greater opportunities not only to local governments in the management of resources in the interests of development financing alone, but is also expected through the program of the Special Autonomy, local communities can be empowered and given the widest possible opportunity to become masters in their own areas. Based on the results of the study factors influence the development of tourism in Raja Ampat, namely, the influence of market trends travelers who recently experienced a shift from mass tourism to special interest tours. Underwater beauty and the beauty of objects as diverse nature indirectly has made the travel services companies flocking to Raja Ampat. Through various programs of travel packages these investors bring tourists to this maritime district. Hoped that investors can benefit not only the beauty of Raja Ampat for profit alone, but what about the presence of investors, development of tourism can provide benefits to local communities in Raja Ampat. For this is the role of investors are required to take more of a role to empower local communities around the attractions are located.Keywords: resource development, the Tourism Industry.